Adverse effects associated with chemotherapy in cancer patients: a survey from Hillah (Iraq) - Al Sa’ady, Amal Talib; Redah Al-Kremy, Noor Abdul; Khdhair, Ola Abbas; Al-Ameedy, Taif Hussein; Khaleq Eidan, Basma Abdel; Rabeea, Haneen; Emad, Saja Salam; Hussien, Teeba Haider (Pharmakeftiki, 2025)
Most cancer patients undergo at least one type of chemotherapy, which is often accompanied by a wide range of adverse effects, from mild symptoms such as nausea, vomiting, and hair loss to life-threatening complications. This retrospective cross-sectional study utilized a paper-based questionnaire targeting cancer patients receiving chemotherapy at the Oncology Center of the Imam Sadiq Teaching Hospital and at the Marjan Medical City Hospital in Hillah, Iraq. The study was conducted between December 6, 2022, and April 30, 2023. A total of 64 patients, aged 1 to 80 years, participated in the study. The most represented age groups were 61–70 years (26.56%), 41–50 years (25%), and 51–60 years (23.43%). The sample included 59.37% females and 40.62% males. Various cancer types were reported, with breast cancer being the most prevalent (40.62%). Both adjuvant and neoadjuvant chemotherapy protocols were documented. Twenty-three distinct adverse effects were identified; the most common included fatigue, exhaustion, and loss of energy (76.56%), anorexia (62.5%), bone and muscle pain (62.5%), vision disorders (57.81%), drowsiness and prolonged sleep (54.69%), sleep disorders (51.56%), as well as nausea and vomiting (50%). All cancer patients (100%) experienced at least one adverse effect as a results of the chemotherapy they received.